The anticipatory and reaction time behaviors of the futsal goalkeeper - da Silva, S. L.; Gemas Neto, E.; dos Santos Palma, G. C.; Sabino Silva Filho, A.; Corrêa, U. C. (Journal of Physical Education, 2020)
This study aimed to investigate the goalkeeper`s anticipatory and reaction time behaviors. For this purpose, 50 kicks performed by male futsal players were analyzed. The time of goalkeeper`s response to a kick was analyzed in relation to the kick outcome, court zone and distance between the goalkeeper and player who performed the kick. The goalkeeper`s anticipation and reaction time behaviors were those below and above 200 ms as the time criterion, respectively, by considering the moment the player began the preparation for kicking to the moment the goalkeeper began to respond to it. Results showed that the goalkeeper performed anticipatory behaviors predominantly when (i) goals were attained and (ii) kicks were performed in the center and attack court`s zones (iii) at a distance ranging from 5.97 to 7.84 meters. In these conditions, the goalkeepers` anticipatory behaviors implied ineffective performances.